Antimicrobial, antioxidant and cytotoxic evaluation of two underutilised food plants: Averrhoa bilimbi L. (Oxalidaceae) and Phyllanthus acidus L. Skeels (Phyllanthaceae). (March 2019) - Seebaluck-Sandoram, Roumita; Lall, Namrita; Fibrich, Bianca; Blom van Staden, Analike; Saleem, Hammad; Mahomoodally, Mohamad Fawzi
Abstract: Averrhoa bilimbi (P1) and Phyllantus acidus (P2) are traditionally used in the management of various diseases in several cultures. Leaf (L) and fruit (F) extracts (decoction, hexane, dichloromethane, ethyl acetate- EtOAc and methanol) were prepared and investigated for their antimicrobial, antioxidant and cytotoxic properties in vitro . P1 and P2 extracts showed broad spectrum activity against ATCC bacterial strains and clinical isolates. P1L and P2F EtOAc extracts inhibited the growth of ATCC strains of S. aureus and V. parahaemolytius (MIC = 250 μg/ml). P1F EtOAc extract was found active against ATCC strains of E. coli and S. aureus (MIC = 250 μg/ml). P1F was active against all tested clinical isolate strains with maximum inhibition against S. aureus ((MIC = 130 μg/ml). Hexane and EtOAc extracts of P2F showed activity against clinical isolate strains of S. aureus ((MIC = 130 and 250 μg/ml, respectively). P2F hexane extract displayed antimicrobial activity against MRSA at MIC value similar to that of streptomycin (250 μg/ml). Furthermore, the antioxidant activity of the different extracts was assessed using DPPH, ABTS and the FRAP assay. The cytotoxicity of the decoction and methanol extracts were also determined using normal adult African green monkey kidney cells (Vero cells). Leaf decoction of P1 showed DPPH radical scavenging activity at an IC50 of 5.30 μg/ml, which was comparable to the positive control, ascorbic acid (IC50 : 5.89 μg/ml). Leaf extracts of P1 were better hydrogen donors compared to leaf and fruit extracts of P2. The methanol and decoction extracts of P1L showed low activity against the ABTS cation at an IC50 value of 39.26 and 31.68 μg/ml, respectively. The P2L and P2F extracts were unable to scavenge ABTS cation radicals. The FRAP values for P2L and P2F extracts were in the range of 59.83–120.89 and 23.98–90.71 TE μM, respectively. Decoction and methanol extracts showed no toxicity at the highest concentration tested. In conclusion, data amassed from the present investigation could open new avenues for research and may serve as the basis for the development of novel drugs.